THE INFLUENCE OF PARENTAL KNOWLEDGE ON SELF-MEDICATION OF DIARRHEA IN CHILDREN IN BAKI SUB-DISTRICT - Hidayah Karuniawati; Nafik Laili Mukarrohmah (Universitas Muhammadiyah Surakarta, 2026)
Despite the high prevalence of diarrhea in Indonesia, inappropriate self-medication practices among parents remain common, including irrational antibiotic use and delayed medical consultation. This study aims to analyze the association between parental knowledge and self-medication for diarrhea in children in the Baki sub-district, Sukoharjo district, and to analyze the sociodemographic correlation between knowledge and practice of diarrhea self-medication. This study used a cross-sectional design to assess parental knowledge and self-medication practices at a single point in time using a structured and validated questionnaire, which consisted of sociodemographics, knowledge, and practice. The inclusion criteria were conducting self-medication for diarrhea, reading, writing, communicating, and being willing to be respondents. The exclusion criteria were health workers. Spearman's rank correlation was used to analyze the correlation between age, education level, and income to knowledge and practice. Chi-Square was used to analyze the association of sociodemographics (gender, occupation, marital status) with knowledge and practice. During the study, the questionnaires were distributed to 384 parents who had self-medicated diarrhea in their children. The average knowledge and practice scores were 83.76 ± 12.15 and 78.78 ± 8.86, respectively. Analysis with Spearman-Rank Correlation found that education level is significantly correlated to knowledge and practice (P value < 0.05), with a positive correlation. Occupation was significantly associated with knowledge (p value 0.036).